Pengaruh Pembiayaan Mudharabah Dan Musyarakah Terhadap Return On Asset BPRS Di Indonesia - Faris Kurnia Hakim; Mauizhotul Hasanah (Jurnal Ekonomi, 2020)
As an intermediary institution, BPRS has facilities in the field of financing where Islamic banks channel funds obtained from the public in the form of deposits. This research was conducted to determine the effect of mudharabah and musyarakah financing simultaneously and partially on the Return On Assets of Islamic People's Financing Banks in Indonesia. The object of research is all Islamic People's Financing Banks in Indonesia from January 2016 to December 2018. The research approach used is a quantitative approach. The analysis technique used is multiple linear regression or OLS (Ordinary Least Squares). The results of this study are that financing using mudharabah and musyarakah contracts simultaneously does not have a significant positive effect on the Return on Assets of Islamic People's Financing Banks in Indonesia. Mudharabah financing partially does not have a significant positive effect on the Return on Assets of the Islamic People's Financing Bank in Indonesia. Musyarakah financing partially does not have a significant negative effect on the Return On Assets of the Islamic People's Financing Bank in Indonesia.